PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VI MI HIFDZUL QUR’AN - Salsabila Annisa Fitri; Annisa Fitri, Salsabila; Dwi Puspita, Ryan (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
This research is motivated by the low learning outcomes of grade VI students of MI Hifdzul Qur’an. The problem formulation in this study is how the application of the make a match type cooperative learning model can improve student’s learning outcomes. The purpose of this study was to analyze the application of the make a match type cooperative learning model in improving the learning outcomes of grade VI students of MI Hifdzul Qur’an. This research uses descriptive qualitative research. The subjects in this study were a teacher and 6th grade students of MI Hifdzul Qur’an totaling 26 students. The data collection techniques used were observation, interview, and documentation. The data analysis techniques used were data condensation, data presentation, and conclusion drawing. The results showed that the application of the make a match type cooperative learning model was carried out with steps including a) the teacher prepares question cards and answer cards; b) students get one question card and one answer card; c) students are given the opportunity to find answer; d) students look for the appropriate card pair; e) finally conclude together the fraction and decimal material. The evaluation stage that the make a match type cooperative learning model is effective to be implemented in mathematics subjects of grade VI MI Hifdzul Qur’an. Based on the hypothesis that has been formulated, it has been proven that in the overall learning activities conducted by the researcher in terms of planning, implementation, and evaluation, the application of the make a match type cooperative learning model can effectively improve the learning outcomes of sixth-grade students at MI Hifdzul Qur’an.